Popular Cinema as Political Theory Idealism and Realism in Epics, Noirs, and Satires - Nelson, John S.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2013)
The book presents cinematic case studies in political realism versus political idealism, demonstrating methods of viewing popular cinema as political theory. The book appreciates political myth-making in popular genres as especially practical and accessible theorizing about politics.
Keywords: Science; Science; Science, general